Black writers, white publishers : marketplace politics in twentieth-century African American literature - Young, John K. (John Kevin), 1968- (University Press of Mississippi, 2006)
"In this book, John K. Young presents the first book-length application of editorial theory to African American literature. Focusing on the manuscripts, drafts, book covers, colophons, and advertisements that trace book production, Young expands upon the concept of socialized authorship and demonstrates how the study of publishing history and practice and African American literary criticism enrich each other."--Jacket